The Outdoor Renaissance: Assessing the Impact of the COVID-19 Pandemic upon Outdoor Recreation Visitation, Behaviors, and Decision-Making in New England's National Forests. Issue 10 (3rd October 2022) - Ferguson, Michael D.; McIntosh, Kyle; English, Donald B. K.; Ferguson, Lauren A.; Barcelona, Robert; Giles, Georgia; Fraser, Olivia; Leberman, Marianne
Abstract: The COVID-19 pandemic has profoundly changed outdoor recreation. As a result of the pandemic, parks and protected areas around the world have witnessed dramatic increases in recreation visitation. While various studies have examined this premise, this is one of the first to examine the influence of the COVID-19 pandemic upon recreation visitation across an entire parks and protected areas system in New England, utilizing both spatial and temporal scales. Study findings provide empirical evidence to inform future research and theory related to the social-ecological systems and recreation opportunity spectrum frameworks. A unique combination of primary, secondary, and geospatial data was used to explore recreation visitors' decision-making, behaviors, and visitation trends during the pandemic. Inferential and regression analyses suggest overall recreation visitation increased by ∼61% (2+ million additional site visits) during the summer of 2020 at the height of the pandemic. Moreover, significant changes in visitation, site, and geo-spatial characteristics were observed for both in-state and out-of-state visitors during the pandemic. This research validates the influence of the pandemic upon parks and protected areas in the United States.